CPWF publication policies and guidelines: Version 1.2 - Victor, Michael; Brakel, Martin L. van; Bayot, Ruvicyn S. (CGIAR Challenge Program on Water and Food, 2011)
The Challenge Program on Water and Food (CPWF) was launched in 2002 as a reform initiative of the Consultative Group on International Agricultural Research (CGIAR). The CPWF aims to increase the resilience of social and ecological systems through better water management for food production (crops, fisheries, and livestock). Since 2002, the program has evolved from a range of research projects to an integrated research program that focuses on specific development challenges in six river basins around the world: Andes, Ganges, Limpopo, Mekong, Nile and Volta. Publishing and documenting research is an important part of the research for development process. It is increasingly recognized that interim results can be important for development practitioners and that communication strategies need to be integrated from the beginning of the research process rather than seen as a by-‐product For this reason, the CPWF strongly encourages the publication of research results, both intermediary and final. It is important to share the CPWF's findings and demonstrate our achievements to our stakeholders, extension agents, donors, policy makers, and other researchers.The guidelines should be seen as a complement to the CPWF Information and Communication Strategy and a range of other guidelines that have been developed including: • Internal knowledge-‐sharing guidelines; • Identity guidelines (to be developed); and • Working Paper series, notes for contributors. The guidelines are intended for CPWF partners working in projects or in the Topic Working Groups. These policies and guidelines should be seen as a work in progress and will be updated as and when necessary